Hovendulcisic acid A-D: four novel ceanothane-type triterpenoids from Hovenia dulcis stems with anticancer properties - Yang, Jianzhan; Cai, Wanna; Wu, Fan; Xu, Shengmei; Zhang, Xiaoqi; Liu, Bo; Xu, Fangfang (Frontiers in Chemistry, 2024)
Sixteen ceanothane-type triterpenoids, including four new compounds—hovendulcisic acids A–D (1–4) —were purified from the stems of Hovenia dulcis Thunb. The structures of 1–4 were confirmed by comprehensive means including ECD and quantum chemical calculations. Putative biosynthetic pathways of 1–16 were proposed, and 3, 5, and 15 exhibited antitumor activity on A549 and MDA-MB-231 cells.